The effects of different stress on intestinal mucosal barrier and intestinal microecology were discussed based on three typical animal models - Guo, Junfeng; Lou, Xiaokun; Gong, Wenyan; Bian, Jing; Liao, Yuhan; Wu, Qi; Jiao, Qibin; Zhang, Xingwei (Frontiers in Cellular and Infection Microbiology, 2022)
Recent studies have revealed that the effect of intestinal microecological disorders on organismal physiology not limited to the digestive system, which provides new perspectives for microecological studies and new ideas for clinical diagnosis and prevention of microecology-related diseases. Stress triggers to impairment of intestinal mucosal barrier function, which could be duplicated by animal models. In this paper, pathological animal models with high prevalence and typical stressors, corresponding to three major stressors of external environmental factors, internal environmental factors and social psychological factors, respectively exampled by burns, intestinal ischemia-reperfusion injure (IIRI) and depression models, were selected. We summarized the construction and evaluation of these typical animal models and the effects of stress on the organism and intestinal barrier, as well as systematically discussed the effects of different stresses on the intestinal mucosal barrier and intestinal microecology.